Oxygenation Responses While Wearing the Elevation Training Mask During an Incremental Cycling Test. Issue 7 (July 2021) - Romero-Arenas, Salvador; López-Pérez, Emilia; Colomer-Poveda, David; Márquez, Gonzalo
Abstract : Abstract: Romero-Arenas, S, López-Pérez, E, Colomer-Poveda, D, and Márquez, G. Oxygenation responses while wearing the elevation training mask during an incremental cycling test. J Strength Cond Res 35(7): 1897–1904, 2021—The Elevation Training Mask 2.0 (ETM) is a commercial training mask that purportedly simulates altitude training, although their effects have not been conclusively demonstrated. Therefore, the purpose of this study was to evaluate the influence of wearing the ETM on muscle and brain oxygenation responses during a maximal incremental cycling test, as well as the influence of this device on the heart rate (HR) response, perception of effort (rating of perceived exertion [RPE]), arterial oxygen saturation (SaO2 ), blood lactate (La + ), and performance (POpeak). Fourteen active males completed an incremental cycling test to volitional exhaustion in 2 separate and counterbalanced conditions, wearing the mask set at 9, 000 feet (i.e., 2743 m) and a control condition (CTR, without ETM). During the trial, muscle and cerebral oxygenation were monitored continuously using near-infrared spectroscopy. Heart rate, RPE, and SaO2 were also recorded from the beginning of the test until the volitional exhaustion. La + was measured at the end of each test. Wearing the ETM significantly reduced the POpeak by −6.9 ± 6.6% ( p = 0.002) and this was accompanied by lower La + values (−12.8 ± 21.6%; p = 0.027). SaO2 was also significantly lower at maximal intensity in comparison with the CTR condition (−1.5 ± 0.3%; p = 0.028). However, both HR and RPE showed a similar trend during both sessions, as well as muscle oxygenation. Nevertheless, the mask caused an increase in brain oxygenation compared with the CTR condition ( p < 0.05). In conclusion, our findings suggest that wearing the ETM causes a pronounced increase in O2 Hb and tHb in the frontoparietal cortex without any change in the muscle oxygenation.